1970
DOI: 10.4314/ejhs.v28i4.11
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Diabetes Mellitus and Associated Factors in Southern Ethiopia: A Community Based Study

Abstract: BACKGROUND: Like in all populations of the world, recently, diabetes became serious health problem in Ethiopian population, as indicated by few community- and institution-based studies. As high as 6.5% diabetes prevalence was reported in Addis Ababa while 5.1% in urban setting and 2.1% in rural setting of Northwest Ethiopia have been reported. This study aimed to provide additional data on the magnitude of diabetes and associated risk factors. The study aimed to determine the prevalence of diabetes in Bona Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
41
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 25 publications
11
41
3
Order By: Relevance
“…4 Studies conducted in Ethiopia showed that the magnitude of type 2 DM in Ethiopia was found to be 5.3%and complications associated with increasing type 2 DM burden are the major causes of morbidity and premature mortality with the consequence of negative economic impact resulted in a public health challenge. 5 Acute kidney injury (AKI), or acute renal failure previously, is characterized by rapid failure of kidney function and is a broad clinical syndrome encompassing various etiologies, including pre-renal azotemia, acute tubular necrosis, acute interstitial nephritis, and acute glomerular renal diseases. 6 AKI is diagnosed by a fast increment in serum Creatinine (Cr), also reflected as a quick diminishing in glomerular filtration rate, within a short time.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…4 Studies conducted in Ethiopia showed that the magnitude of type 2 DM in Ethiopia was found to be 5.3%and complications associated with increasing type 2 DM burden are the major causes of morbidity and premature mortality with the consequence of negative economic impact resulted in a public health challenge. 5 Acute kidney injury (AKI), or acute renal failure previously, is characterized by rapid failure of kidney function and is a broad clinical syndrome encompassing various etiologies, including pre-renal azotemia, acute tubular necrosis, acute interstitial nephritis, and acute glomerular renal diseases. 6 AKI is diagnosed by a fast increment in serum Creatinine (Cr), also reflected as a quick diminishing in glomerular filtration rate, within a short time.…”
Section: Introductionmentioning
confidence: 99%
“…Peoples living with DM are at more risk for AKI than those without diabetes, mainly type 2 DM is one of the major risk factors for the occurrence of AKI. 5 Peoples living with type 2 diabetes are eight times more likely to develop acute kidney injury as compared to patients without diabetes. 7 Acute kidney injury is a serious disease globally affecting greater than 13 million individuals annually, 85% are living in developing countries.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, this number is estimated to rise to 1.8 million by the year 2030. 14,15 The World Health Organization's report revealed that a trend in the prevalence of diabetes in Ethiopia has been increasing over the past years. According to the 2017 International Diabetes Federation (IDF), the prevalence of type-2 diabetes mellitus in Ethiopian adults was 5.2%.…”
Section: Introductionmentioning
confidence: 99%